(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Refractive amblyopia, especially against the background of hyperopic refraction, is the most common cause of amblyopia in childhood. The aim of the research — to study the results of treatment of refractive amblyopia in children with hyperopic refraction using the video- computer auto-training (VКА) and traditional methods. Material and methods. Studied the results of the treatment method of the VКА with the help of the device «Ambliokor» 50 children with hyperopia and refractive amblyopia and traditional treatment of 50 children with similar disorders. Results. Amblyopia treated in 83 eyes of the children of the main group (83, 0 %). In all other eyes children in this group amblyopia was weak. In the control group amblyopia treated in 32 eyes (32, 0 %) (P< 0.05). In 60 eyes (60, 0 %) children of the main group amblyopia was cured for one course. The conclusions. Conducting video-computer auto-training with the help of the device «Ambliokor» more efficiently than traditional pleoptic treatment.